Teks Eksplanasi Kompleks dalam Media Massa dan Pemanfaatannya Sebagai Materi Ajar - Yuliyana Susanti; Sumarti Sumarti; Kahfie Nazaruddin (FKIP Universitas Lampung, 2019)
The purpose of this study was to describe the structure and the use of linguistic rules in complex explanatory texts in mass media and to design teaching materials for the second grade students of senior high school. This study used a qualitative approach and descriptive method. This study found that the complex explanatory text structure was in accordance with the theory. The linguistic rules of complex explanatory texts which were found were dominated by the use of time-markers because both chronological and causal texts were accompanied by adverbs of time. The teaching material which was produced was the outcome that was suitable for learning to understand the structure and rules of complex explanatory texts in the second grade students of senior high school.Tujuan penelitian ini mendeskripsikan struktur dan penggunaan kaidah kebahasaan teks eksplanasi kompleks dalam media massa dan merancang materi ajar untuk SMA kelas XI. Penelitian ini menggunakan pendekatan kualitatif dan metode deksriptif. Penelitian ini menemukan bahwa struktur teks eksplanasi kompleks yang ditemukan sesuai dengan teori. Kaidah kebahasaan teks eksplanasi kompleks yang ditemukan didominasi dengan penggunaan kata penunjuk keterangan waktu karena baik teks yang bersifat kronologis maupun kausalitas disertai dengan kata penunjuk keterangan waktu. Materi ajar yang dihasilkan ialah outcome yang cocok untuk pembelajaran memahami struktur dan kaidah teks eksplanasi kompleks di SMA Kelas XI.Kata kunci: teks eksplanasi kompleks, media massa, dan materi ajar